The patterns of inbreeding depression in food-deceptive Dactylorhiza orchids - Wróblewska, Ada; Ostrowiecka, Beata; Brzosko, Emilia; Jermakowicz, Edyta; Tałałaj, Izabela; Mirski, Paweł (Frontiers in Plant Science, 2024)
Inbreeding depression (ID) in food-deceptive plants have been reported previously, however, it has not been often proven that selfed seeds germinate better than outbred ones or that selfing affects ID. To resolved these issues, food-deceptive related Dactylorhiza majalis, D. incarnata var. incarnata and D. fuchsii orchids were investigated. Hand pollination treatments and control pollination were conducted. Fruit set, number of seeds per fruit, seed length, number of welldeveloped seeds per fruit, and proportion of in vitro asymbiotic germination seeds, were analyzed in relation to inflorescence levels and used as fitness indicators for these orchids. The ID and pollen limitation were measured. The lowest ID (δ = -1.000) was in D. majalis, and present in combination with a high pollen limitation in its populations. D. fuchsii showed higher ID (δ = 0.366), and D. incarnata var. incarnata weak ID (δ = 0.065), although ID varied between its fitness components. The seed number per fruit differed significantly between the treatments and the inflorescence levels in treatments. This study emphasizes that the breeding system rather than the flower position on the inflorescence shaped the quality and quantity of reproductive output. The ID and its effect on germination of food-deceptive orchid seeds undoubtedly played an important role.